To exchange or not to exchange liquid food: is that the question for foraging leaf-cutting ant workers? - Catalani, Gabriela Christal [UNESP]; Camargo, Roberto da Silva [UNESP]; Mota Filho, Tarcisio Marcos Macedo [UNESP]; Andrade Sousa, Kátia Kaelly [UNESP]; Matos, Carlos Alberto Oliveira [UNESP]; Caldato, Nádia [UNESP]; Nagamoto, Nilson Satoru [UNESP]; Zanuncio, José Cola; Forti, Luiz Carlos [UNESP] (Wiley, 2022)
Leaf-cutting ants forage fresh plants in the field to cultivate the symbiotic fungus in their nests. The trophallaxis rates in leaf-cutting ants may be related to liquid foraging behavior and exchanging liquid food with other ants inside the nest. The liquid foraging and liquid food exchange in laboratory colonies of the leaf-cutting ant Atta sexdens (L.) (Hymenoptera: Formicidae, Attini) were studied to test whether liquid food is transferred to inside-nest workers by foragers. The foragers commonly ingested liquid when provided with a liquid source and performed different behaviors, such as self- and allogrooming, but without food exchange (oral trophallaxis) to the workers inside the nest. The liquid foraging was not related to food exchange with workers inside the nest. We suggest that liquid foraging meets the individual worker needs without liquid exchange among ants inside their colonies.
Keywords: Atta sexdens; behavior; extrafloral nectaries; food exchange; foraging; Formicidae; grooming; Hymenoptera; leaf-cutting ants; liquid food; symbiotic fungus; trophallaxis